2020
DOI: 10.3390/pathogens9080623
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Epstein-Barr Virus DNA in Gastric Biopsies of Pediatric Patients with Dyspepsia

Abstract: In this study, we assessed the presence of Epstein-Barr virus (EBV) in gastric samples derived from pediatric patients with dyspeptic symptoms, aiming to understand whether EBV participates in the development of early gastric lesions influencing chronic inflammation, in conjunction with the Helicobacter pylori (Hp) bacterium. We analyzed EBV load in 236 gastric biopsies derived from 186 pediatric patients with chronic dyspepsia and compared it with EBV serology, Hp load and serology, and with immune cell infil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…12 To date the association EBV and CMV with gastritis have been documented in several case reports or case series. 8,15,20 However, there is little information about the occurrence of HHV-6 infection in the gastrointestinal tract, especially gastritis and its role is not yet well known. In this study, we analyzed the frequency of EBV, CMV, and HHV-6 infections in patients with gastric cancer and chronic gastritis and indicated the correlation between the presence of these viruses with the patient's status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 To date the association EBV and CMV with gastritis have been documented in several case reports or case series. 8,15,20 However, there is little information about the occurrence of HHV-6 infection in the gastrointestinal tract, especially gastritis and its role is not yet well known. In this study, we analyzed the frequency of EBV, CMV, and HHV-6 infections in patients with gastric cancer and chronic gastritis and indicated the correlation between the presence of these viruses with the patient's status.…”
Section: Discussionmentioning
confidence: 99%
“…CMV, another member of the Herpesviridae family has been linked to several cancers, including colorectal cancer, 11 glioblastoma, 13 and lymphatic metastasis 12 . To date the association EBV and CMV with gastritis have been documented in several case reports or case series 8,15,20 . However, there is little information about the occurrence of HHV‐6 infection in the gastrointestinal tract, especially gastritis and its role is not yet well known.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noticing, that EBV is enumerated among human viruses with a proven role in oncogenesis, and the development of autoimmune disorders, as well as immunosuppression [40][41][42][43]. The life cycle of EBV is particularly complex and the virus undergoes the latency phase during which it expresses several genes impacting oncogenesis [44][45][46][47]. Recent studies have shown that EBV DNA is present in large quantities in patients with autoimmune diseases of several etiologies [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…CMV, another member of the herpesviridae family has been linked to several cancers, including colorectal cancer (11), glioblastoma (13) and lymphatic metastasis (12). To date association EBV and CMV with gastritis have been documented in several case reports or case series (8,15,20). However, there is little information about the occurrence HHV-6 infection in the gastrointestinal tract, especially gastritis and its…”
Section: Discussionmentioning
confidence: 99%